Probiotics and prebiotics : current research and future trends - Venema, Koen; Carmo, Ana Paula do (Caister Academic Press, 2015)
Composed of nearly a thousand different types of microorganisms - some beneficial, others not - the human gut microbiota plays an important role in health and disease. This is due to the presence of probiotic or beneficial microbes, or due to the feeding of prebiotics that stimulate the endogenous beneficial microbes (these promote health by stimulating the immune system, improving the digestion and absorption of nutrients, and inhibiting the growth of pathogens). The notable health benefits of probiotic organisms have prompted much commercial interest, which in turn has led to a plethora of r.